PENERAPAN INFRASTRUKTUR HIJAU DI TPS3R DESA KELIKI, KECAMATAN TEGALLALANG, KABUPATEN GIANYAR, PROVINSI BALI - Suparta, I Wayan; Dewi, I G.A. Wulan Krisna; Suparta, I Wayan Darya (Politeknik Negeri Semarang, 2024)
Keliki Village, Tegallalang District, Gianyar Regency, Bali Province, has a TPS3R which was initially considered less attractive by the local community because it was considered to interfere with tourism. This background encouraged the implementation of green infrastructure in the TPS3R of Keliki Village as an effort to improve the quality of the environment and the aesthetics of the area. The problems faced were the low public awareness of sustainable environmental management and the lack of skills of local craftsmen in implementing green infrastructure principles. The purpose of this activity was to rearrange the TPS3R according to green infrastructure standards, while providing training to local craftsmen so that they are able to work on infrastructure projects properly. The method used involved collaboration between the Bali State Polytechnic, the Keliki Village Government, and the Yowana Bakti Keliki BUMDES, with training in installing environmentally friendly geotextile-based paving as the main focus. The Village Government provided the facilities, infrastructure, and materials needed, while the BUMDES facilitated labor from local banjars. The results of this activity showed an increase in the skills of local craftsmen and the arrangement of the TPS3R which was more visually attractive, in accordance with the concept of green infrastructure. In conclusion, the implementation of green infrastructure in TPS3R has not only succeeded in improving environmental quality, but also changed the image of TPS3R into an environmentally friendly area and more attractive to the community and tourists.